Physical Well-Being Needs of Bone Cancer Patients during Treatment in the Hospital: A Qualitative Study - Priyanto, Priyanto; Fauzi Kamal, Achmad; Dahlia, Debie; Besral, Besral (Nurse Media Journal of Nursing, 2023)
Background: Bone cancer patients undergoing hospitalization require support to manage physical challenges for optimal healing and recovery. The physical aspects experienced by the patients significantly affect their physical well-being. Addressing these aspects is essential for nurses in providing care. However, comprehensive assessments of bone cancer patients’ physical needs have not been thoroughly explored. Purpose: This study aimed to explore the physical well-being needs of patients with bone cancer undergoing hospitalization. Methods: This qualitative study with a phenomenological approach was conducted among 14 bone cancer patients selected through purposive sampling. The criteria included patients with a primary cancer diagnosis, undergoing hospitalization at a cancer center, and having good orientation and verbal communication abilities. In-depth interviews were employed to delve into the patients’ well-being needs. To triangulate the data, 12 cancer nurses were involved. Data analysis utilized the Creswell method.Results: This study found chronic pain and bone lumps as fundamental physical challenges, leading to disruptions in physical movement, sleep disturbances, and dependency on others for self-care. Six themes emerged regarding the physical well-being needs of hospitalized bone cancer patients: goals and needs for physical well-being, need for pain management, need for physical mobility, need for sleep and rest, need for self-care, and the meaning of physical well-being for patients. Physical well-being provides a significant meaning in achieving nursing goals.Conclusion: This study shows the significance of addressing pain management, physical mobility, sleep and rest, and self-care for the physical well-being of bone cancer patients. Nurses should be able to identify various physical complaints and help improve the physical well-being of bone cancer patients.